Implementasi manajemen pembelajaran Kelas Inklusi di SMA Kartini Batam - Putri, Tammara Anwari; Hidayati, Dian; Sukirman, Sukirman (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Since its inception, Kartini High School in Batam City has been a public school that provides academic services to the general student category. In 2012, some students were identified as having special needs. Since 2012, Kartini Batam High School has accepted nine students with special needs. This research aims to analyze the implementation of inclusive education at SMA Kartini Batam. This research is a descriptive qualitative research, and according to the place, this research is a field research. Descriptive research describes a situation or describes a situation under study. Data collection techniques using observation, interviews, and reduced documentation are then draw conclusions. The process of data analysis is done by qualitative analysis. The research results are steps taken by the school, namely planning, organizing, and implementing, as well as comprehensive evaluation to improve students’ learning outcomes.